Re-utilization of Sub-optimal Used-planting Media to Cultivate Black Rice in the Pot - ES Halimi; MN Lestari; C Syakirin; I Pales (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
Beside reducing production cost, re-utilization sub-optimal used planting media was environmentally good practice, especially when the plants were cultivated in the pots. This research incorporated black rice accession that had high economic value. The plants were cultivated in 10-kg pots, arranging in Randomized Block Design with three replications, each consisted of 5 pots. The treatments were weight-based additions of local organic soil and commercial organic fertilizer of 5 %, 10 %, 15 %, and 0 % (no-addition). Result of this research indicated that 10 % addition of local organic soil was considered enough to cultivated black rice in the pots. The plants were observed to grow normal with plant height reached 150 cm, consisted of 70 clumps and produced 56.52 g dry seeds per pot, equivalent to 11.69 ton per ha. In percentage, addition of 5, 10 and 15 % local organic soil, resulted in 33-53 % increase in number of mature panicles, 33-56 % increase in total number of seeds, 123-232 % increase in number pithy seeds, and 106-289 % increase in weight of dry seeds per pot.